On the microtwinning mechanism in a single crystal superalloy - Barba, D; Alabort, E; Pedrazzini, S; Collins, D; Wilkinson, A; Bagot, P; Moody, M; Atkinson, C; Jérusalem, A; Reed, R (Elsevier, 2017)
The contribution of a microtwinning mechanism to the creep deformation behaviour of single crystal superalloy MD2 is studied. Microtwinning is prevalent for uniaxial loading along 〈011〉 at 800°C for the stress range 625 to 675 MPa and 825°C for 625 MPa. Using quantitative stereology, the twin fraction and twin thickness are estimated; this allows the accumulated creep strain to be recovered, in turn supporting the role of the microtwinning mode in conferring deformation. Atom probe tomography confirms the segregation of Cr and Co at the twin/parent interface, consistent with the lowering of the stacking fault energy needed to support twin lengthening and thickening. A model for diffusion-controlled growth of twins is proposed and it is used to recover the measured creep strain rate. The work provides the basis for a thermo-mechanical constitutive model of deformation consistent with the microtwinning mechanism.